COMPREHENSIVE ANALYSIS OF MOTHER-CHILD BONDING DURING POSTNATAL CARE - NAFLA NAIF ALOTAIBI, SULTAN MODEATH ALBOGMI, KHALED NASSER ALOTAIBI, AYOOB SAUD ALDRAWISH, MAZEN SAEED ALZAHRANI, ELHAM ALSHEHRI, MAJED MUQBIL A ALOTAIBI, MOHAMMED TURKI ALHARBI (Chelonian Research Foundation, 2022)
Mother-child attachment during postpartum care is a significant factor for mammary and baby emotional and psychological evolution. The paper is intended to present the ecology study of mother-baby bonding in the postpartum period as it explores the factors that determine the bonding, the importance of the early interactions in baby development, and the interventions to foster the bonding process for the child. An evaluation of literature and empirical analysis summarizes the modern state of parent-baby bonding, identifies observed gaps in research, and provides reasons for improved bonding outcomes. Data reveal the importance of nurturing conditions, skin-to-skin contact, breastfeeding, and parental education as critical factors that strengthen a maternal-infant bond. Keywords: mother-child bonding, postnatal care, breastfeeding, parent education.